Collaborative cytometric inter-laboratory ring test for probiotics quantification - Jordal, Peter Lüttge; Diaz, Marcos González; Morazzoni, Carlotta; Allesina, Serena; Zogno, Daniele; Cattivelli, Daniela; Galletti, Serena; Guidesi, Elena; Warzée, Jean-Pol; Pane, Marco (Frontiers in Microbiology, 2023)
Probiotics are live microorganisms that, when administered in adequate amounts, confer a health benefit on the host (Hill et al. 2014). From this definition, accurate enumeration of probiotic products is a necessity. Nonetheless, this definition does not specify the methods for assessing such viability.Colony forming units is the de facto gold standard for enumerating viable in probiotic products (Weitzel et al. 2021). The notion of microbial viability has been anchored in the concept of cultivability, which refers to a cell's capacity to replicate and form colonies on agar media (Fiore, Arioli, and Guglielmetti 2020). However, there is a growing consensus that the term "viability" should not be exclusively tied to the ability to cultivate cells (Wendel 2022). For example, bacterial cells can exist in a Viable But Non-Culturable (VBNC) state, characterized by the maintenance of characteristics such as membrane integrity, enzymatic activity, pH gradients, and elevated levels of rRNA, despite losing the ability to form colonies (Breeuwer and Abee 2000).Herein we present the results of a collaborative inter-laboratory ring test for cytometric bacterial quantification. Specifically, membrane integrity fluorescence flow cytometry (FFC) method and the newer impedance flow cytometry (IFC) method have been used. Both methods interrogate single cells in solution for the presence of intact membranes. FFC exploits fluorochromes that reflect the presence or absence of an intact membrane. IFC probes membrane integrity in a label-free approach by detecting membrane-induced hindrances to the propagation of electricity.A performance ring-test and comparison design on the FFC method showed that the method is robust against the exchange of equipment, procedures, materials, and operators. After initial method optimization with assessments of rehydration medium, wake-up duration, and phase shift gating on the individual strains, the IFC method showed good agreement with the FFC results. Specifically, we tested 6 distinct species of probiotic bacteria (3 Lactobacillus and 3 Bifidobacterium strains) finding good agreement between FFC and IFC results in terms of total and live cells. Together, these results demonstrate that flow cytometry is a reliable, precise, and user-friendly culture-independent method for bacterial enumeration.